Human Resource Management Strategies to Improve Performance in the Digital Era - Eliza, Eliza (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
In the ever-growing digital era, human resource management (HR) strategies have become very important to improve organizational performance and efficiency. This research focuses on the implementation of digital technology in various HR processes, including automation of administrative tasks, technology-based recruiting, and performance management. This digitalization not only increases operational efficiency, but also provides better insight into managerial decision making. One of the key aspects of this research is the development of employees' digital skills. In a world of work that is increasingly dependent on technology, having employees who are digitally skilled is an invaluable asset. This includes training in data analysis, programming, and utilizing the latest digital platforms. This training not only improves individual performance, but also strengthens the organization's ability to compete in the global market. This research also highlights the importance of remote work as an HR strategy in the digital era. The global pandemic has accelerated the adoption of remote work models, showing that flexibility in work can improve employee productivity and work-life balance. Additionally, remote work opens up opportunities for organizations to access global talent without geographic limitations. Finally, this research emphasizes the importance of creating an adaptive and collaborative organizational culture. This culture that encourages innovation and continuous learning is essential to taking full advantage of the benefits of the digital era. Through this approach, organizations can not only survive, but also thrive amidst rapid and unpredictable change.